Immigrant and Refugee COVID-19 Vaccination Attitudes in South Philadelphia - Posego, Lauren; Anshel Kenkare; Makala Wang; Omar El Fadel; Morgan Hutchinson (International Journal of Medical Students, 2023)
Immigrants and refugees have been disproportionately affected by the COVID-19 pandemic; therefore, it is important to determine the specific factors that are promoting vaccination in the immigrant and refugee populations to develop equitable health services. This study surveys the attitudes toward COVID-19 vaccination and vaccine mandates in the Southeast Asian and Hispanic immigrant and refugee populations in South Philadelphia. A questionnaire was administered to all patients receiving the COVID-19 vaccine during six clinic days from November 15th-31st 2021. Investigators asked participants about their intention behind vaccination, barriers to access, work requirements regarding COVID-19 vaccination, and attitudes toward vaccine mandates. For people receiving their booster vaccine, the most cited reasons for getting vaccinated were protecting their health (75.4%) and travel (11.0%), whereas most people receiving their first or second vaccine were most motivated by vaccine mandates at work (34.6%) and health (30.8%). Staying healthy or “health” was the most common reason for getting vaccinated among people receiving their booster vaccine (74.8%) which was significantly higher than the proportion of people getting their first or second vaccine (30.7%) (p<0.05). As people continue to get vaccinated, determining motivating factors can help promote appropriate messaging. The results of the study suggest that, in a clinical setting geared towards Southeast Asian and Hispanic immigrants and refugees, those getting their first and second dose were motivated by work mandates more than health at the time of the study, whereas those adults receiving their booster are most motivated by health and safely traveling. As we continue to aim for mass vaccination, vaccine mandates appear to be an effective method of motivating people to get their first and second dose.